2011
DOI: 10.3109/15419061.2011.617854
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin and des-Arg10-kallidin enhance the adhesion of polymorphonuclear leukocytes to extracellular matrix proteins and endothelial cells

Abstract: Bradykinin-related peptides (kinins) are well known to contribute to leukocyte recruitment to infl ammatory foci; however, a role of these universal pro-infl ammatory mediators in the fi rst step of this process, i.e. the leukocyte adhesion to endothelial cells, is not well understood. In this work we found that bradykinin and des-Arg 10 -kallidin enhance the adhesion of polymorphonuclear bloods cells (PMN) to fi brinogen and fi bronectin. Also, the PMN adherence to endothelial cells of HMEC-1 line strongly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…The analyzed immortalized endothelial cell line isolated from the human umbilical vein expresses both receptors endogenously, confirming earlier reports of the expression of these receptors in endothelial cells (Zarei et al, 2006;Terzuoli et al, 2014). In accordance with previous reports (Schuschke et al, 2001;Guevara-Lora et al, 2011), the current study indicated that BK increased the PMN adhesion to endothelial cells, with a maximal response observed after 6 hours of cell incubation (Fig. 1A).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The analyzed immortalized endothelial cell line isolated from the human umbilical vein expresses both receptors endogenously, confirming earlier reports of the expression of these receptors in endothelial cells (Zarei et al, 2006;Terzuoli et al, 2014). In accordance with previous reports (Schuschke et al, 2001;Guevara-Lora et al, 2011), the current study indicated that BK increased the PMN adhesion to endothelial cells, with a maximal response observed after 6 hours of cell incubation (Fig. 1A).…”
Section: Discussionsupporting
confidence: 93%
“…Isolated PMN were suspended in RPMI-1640 medium and loaded with Cell Tracker Red CMTPX in RPMI for 30 min at 37°C, following the manufacturer's instructions, and then placed on a monolayer of endothelial cells stimulated as described below. Detailed description of the cell adhesion analysis was provided elsewhere (Guevara-Lora et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Involvement of kinin receptors in chemotaxis, cell migration, and trafficking was proposed [Koyama et al, ; McLean et al, ; Sainz et al, ; Lu et al, ; Yang et al, ]. We have recently reported that the adhesion of polymorphonuclear leukocytes (PMN) can be enhanced by kinin peptides [Guevara‐Lora et al, ]. PMN adhesion to the endothelial cells was regulated by BK and, even more remarkably, by B1R agonists.…”
mentioning
confidence: 99%